1991
DOI: 10.1017/s0016756800022123
|View full text |Cite
|
Sign up to set email alerts
|

The Nod Glas décollement of the Welsh Basin

Abstract: Structural, petrographic and metamorphic evidence is presented for localized end-Caledonian (Acadian) décollement within a ‘black shale’ formation in the central Welsh Basin, close to the Caradoc–Ashgill boundary. Similar detachments are probably widespread in other parts of the, paratectonic Caledonides with upright folds and cleavage, particularly in sequences with strong viscosity contrasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Woodcock (1990) combined this with local evidence of early Ashgill tectonic activity in Wales to postulate a basin-wide unconformity in Wales marking the base of a Powys Supergroup. However, Pratt (1991) noted that sedimentation may have been continuous but reduced, at least in the central parts of the basin, and that the Nod Glas was a level of end-Caledonian d6collement, thus making the continuity or otherwise of upper Caradoc to lower Ashgill successions difficult to establish. This study suggests that the palaeontological gap represents marked biofacies variation rather than absence of strata, and that sedimentation may have been more widely continuous across the Caradoc-Ashgill boundary in Wales than has been previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…Woodcock (1990) combined this with local evidence of early Ashgill tectonic activity in Wales to postulate a basin-wide unconformity in Wales marking the base of a Powys Supergroup. However, Pratt (1991) noted that sedimentation may have been continuous but reduced, at least in the central parts of the basin, and that the Nod Glas was a level of end-Caledonian d6collement, thus making the continuity or otherwise of upper Caradoc to lower Ashgill successions difficult to establish. This study suggests that the palaeontological gap represents marked biofacies variation rather than absence of strata, and that sedimentation may have been more widely continuous across the Caradoc-Ashgill boundary in Wales than has been previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…Superimposed on this gradual increase, however, is a drop between the Ceiswyn and Nod Glas formations that is confirmed by a Student r-test. It has been noted that the pyritous and carbonaceous Nod Glas Formation acted as an horizon of mild decollement and Pratt (1991) has shown that maximum accommodation took place in the overlying Broad Vein and Narrow Vein formations, especially in the Corris Anticline, resulting in high anchizonal to low epizonal slates. Grade, however, is also seen to fall along strike to both southwest and northeast within these formations, with values (see Fig.…”
Section: B the Influence Of Strain On Crystallinitymentioning
confidence: 99%
“…Observations by Jones & Pugh (1935), however, suggested that intense shearing had occurred in the Nod Glas Formation underlying the succession of the Corris Slate Belt. Decollement within the Nod Glas Formation has recently been described by Pratt (1991). Decollement within the Nod Glas Formation has recently been described by Pratt (1991).…”
Section: Introductionmentioning
confidence: 99%